Objective assessment of shared plate eating using a wearable camera in urban and rural households in Ghana - Domfe, Christabel A.; McCrory, Megan A.; Sazonov, Edward; Ghosh, Tonmoy; Raju, Viprav; Frost, Gary; Steiner-Asiedu, Matilda; Sun, Mingui; Jia, Wenyan; Baranowski, Tom; Lo, Benny; Anderson, Alex K. (Frontiers in Nutrition, 2024)
Background: Shared plate eating (SPE), defined as two or more individuals eating directly from the same plate or bowl, is a common household food consumption practice in many Low-and Middle-Income Countries (LMICs). Examination of household engagement in SPE remains largely unexplored, highlighting a gap in research when interpreting dietary information obtained from these settings. The dearth of research into SPE can be attributed to the inherent limitations of traditional dietary assessment methods which constrain their usability in settings where SPE is common.The wearable camera captured eating dynamics within households that would have likely been missed or altered by traditional dietary assessment methods. Obtaining reliable and accurate data is crucial for assessing dietary intake in settings where SPE is a norm. Abbreviations used: 24hdr (24-hour dietary recall), AIM (Automatic Ingestion Monitor), IPE (Individual Plate Eating), LMIC (Low-and Middle-Income Country), HIC (High Income Country), SPE (Shared Plate Eating), WD1 (Weekday 1), WD2 (Weekday 2), WE (Weekend Day)